ANALISIS STRATEGI PEMERINTAH PUSAT DAN DAERAH DALAM MENGHADAPI MEA (MASYARAKAT EKONOMI ASEAN) 2015 - Sari, Dian Indah (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2014)
This research aims to know the strategy  of the central government and local in the face of MEA 2015. By knowing the strategy of the central government and local Indonesian society is expected to be able to prepare themselves to face MEA 2015. This study used a descriptive analytical and literature study with secondary data which source books, journals, literature, reports and official information from ASEAN secretary in  Jakarta or other sources obtained from the internet related to the above theme.  Strategy and preparation Indonesia in order to deal with liberalization of the system applied ASEAN still less than optimal. But Indonesia with potential resources abundant have brought the movement to a more advanced again. This is evidenced by the growing recognition of international environmental  against the existence of Indonesia on a positive track. It can be concluded that Indonesia is able to and ready to face the realization AEC 2015. Keywords: AEC, ASEAN Community, Strategy of national and local government to face MEA